Traction System Development for Intercity EMUs - JIAO Jinghai; CAO Jiang; LIU Jiangtao; SUN Ning; RONG Zhilin (机车电传动)
Railway and traction system features of intercity EMUs were analyzed, and the ability requirement of the EMU waspointed out. Traction platform scheme of CRH6 series intercity EMUs was expounded in detail, and the simulation and test of system andparts validated the good performance of the traction system.